If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4w + 3 = 23 Reorder the terms: 3 + 4w = 23 Solving 3 + 4w = 23 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4w = 23 + -3 Combine like terms: 3 + -3 = 0 0 + 4w = 23 + -3 4w = 23 + -3 Combine like terms: 23 + -3 = 20 4w = 20 Divide each side by '4'. w = 5 Simplifying w = 5
| y=3+(ln^2)*x | | 5(-x-4)=30 | | x^2+2=2x+2 | | 71=35+(x*.18) | | 2x-c^2=0 | | 41=35+(x*.18) | | 80+1x+109=180 | | 6c-3+5(c-4)+2=4c+7(c-3) | | 4x-3-3x-2-x=10 | | 7x+30y=-7 | | (7+x)*(4+x)=100 | | (7x+1)(7x-1)-49(x+1)=4-98x | | x^2+6x^3+2x^2=0 | | x^2-1/3-x | | x^2-1/3-c | | 12+4x+3+7x= | | 4m-(m+3)=5m+2(-m+10) | | a^(-5)/a^7 | | a^(-5)/a67 | | T-2=19 | | -6=(3/4)h | | a^5/a^7 | | -6=3/4h | | 3x^2-12x-16/x-2 | | x+x(2x+1)=31 | | 4-(abs(2x))=3 | | 2=1.06 | | 6h^2+8h-9=0 | | 2x+8x-(6x+9)= | | 18-(2y+14)= | | 4/3y=1/8 | | Y-9=-1(x+6) |